Implementasi Nilai-Nilai Kearifan Lokal dalam Pembelajaran Sejarah Sumatera Utara di Prodi Pendidikan Sejarah Universitas Islam Sumatera Utara - Damanik, Raudhotul Jannah; Nababan, Surya Aymanda; Pulung Sumantri; Muhammad Ricky Hardiyansyah; Muhammad Adika Nugraha; Abdul Azis (Medan Resource Center, 2023)
The purpose of this research is to understand how the values of local wisdom are implemented in history education. Additionally, it aims to explore how character education based on local wisdom is applied. This is because the research problems are related to the implementation of local wisdom values in history education and character education based on local wisdom. The method used in this research is qualitative. Thus, it can be concluded that the learning model is a teaching technique used by teachers to teach a specific subject matter, and the selection of a model must be adjusted to the lesson material first. In relation to the sequence of material presentation, the values of local wisdom can also be applied in the models used by lecturers. Local wisdom is an integral part of a society's culture and cannot be separated from the language of that society. One of the issues that needs attention in the current era of globalization is the issue of nationalism. The purpose of writing this article is to help teachers apply or implement elements of local wisdom.